2021
DOI: 10.1123/jpah.2021-0243
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices for Meta-Reviews in Physical Activity and Health Research: Insights From the Physical Activity Guidelines for Americans Advisory Committee Scientific Report

Abstract: Background: Systematic reviews (SRs) and meta-analyses (MAs) have proliferated with a concomitant increase in reviews of SRs/MAs or “meta-reviews” (MRs). As uncovered by the 2018 US Physical Activity Guidelines Advisory Committee (PAGAC), there is a paucity of best practice guidance on MRs on physical activity health-related research. This manuscript aims to fill this gap. Methods: In total, the PAGAC conducted 38 literature searches across 3 electronic databases and triaged 20,838 titles, 4913 abstracts, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Negative everyday habits such as lack of exercise and a hypercaloric diet not only lead to widespread chronic diseases and escalating medical expenses but also inflict considerable financial damage in the workplace [54][55][56][57][58][59]. Well before the onset of obesity and chronic illnesses (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative everyday habits such as lack of exercise and a hypercaloric diet not only lead to widespread chronic diseases and escalating medical expenses but also inflict considerable financial damage in the workplace [54][55][56][57][58][59]. Well before the onset of obesity and chronic illnesses (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Well before the onset of obesity and chronic illnesses (e.g. diabetes, fatty liver, circulatory diseases), employees often experience reduced resilience, declining productivity and a significant drop in performance [33,44,57,[60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…But even at this meta-level, it is difficult to keep track of the existing research and draw meaningful conclusions. For example, searches of PubMed conducted by Pescatello et al [34] revealed 76´768 "reviews on physical activity" (from 1843 to 2021) and 6076 "systematic reviews (SRs) and meta-analyses (MAs) on physical activity" (from 1996 to 2021), as well as several other types of reviews published by 2021. Consequently, meta-reviews are used to summarize evidence on the meta-level [35] systematic reviews of systematic reviews and meta-analyses ("reviews of reviews") [6].…”
Section: Behavior Change Techniquesmentioning
confidence: 99%
“…In summary, there is an entire taxonomy of behavior change techniques and a wealth of empirical studies investigating their effectiveness for health promotion. Further, there is no lack of well-defined and high research standards [39], nor of recommendations for designing and examining interventions in a methodologically rigorous way [34,40]. And yet progress in health behavior change urgently needs to be accelerated and to become more pronounced to match the scale of the problem [41].…”
Section: Behavior Change Techniquesmentioning
confidence: 99%
“…On the other hand, Physical Fitness (PF) is the ability to perform an exercise with the correct development of physiological and psychological skills [7,8], and previous studies have shown that a poor level of PF should be identified as a "warning sign" in children's health [9]. In fact, PF has an inverse relation with obesity and the risk of CVD, and it is also positively related to skeletal and metabolic health [7,10].…”
Section: Introductionmentioning
confidence: 99%